Prognostic value of molecular breast cancer subtypes based on Her2, ESR1, PGR and Ki67 mRNA-expression in muscle invasive bladder cancer - Kriegmair, Maximilian; Worst, Thomas; Ritter, Manuel; Böhmer, Christopher; Weis, Cleo-Aron Thias; Erben, Philipp (Translational oncology, 2018)
INTRODUCTION: Gene expression analyses have identified similarities between bladder and breast cancer, where clinical risk stratification is based on Her2, ESR1, PGR and Ki67 expression. The aim of the study was to assess the respective marker gene expression in patients treated with radical cystectomy for muscle-invasive bladder cancer (MIBC) and to evaluate the applicability of breast cancer subtypes for MIBC risk stratification. MATERIALS & METHODS: 102 patients treated with radical cystectomy for MIBC were assessed. Using routine FFPE tissue and an IVD validated kit, mRNA expression was measured by single step RT-qPCR. Partition test were employed to define cut-off values for high or low marker gene expression. Association of expression with outcome was assessed using Kaplan-Meier analysis and multivariate cox regression analysis. Finally, we performed validation of our results in the MD-Anderson cohort (n=57). RESULTS: Cancer specific survival (CSS) was impaired in patients with high gene expression of Her2 (P=0.0009) and ESR1 (P=0.04). In the multivariate regression model Her2 expression remained significant for the prediction of CSS (HR=2.11, CI 1.11-4.21, P=0.024). Furthermore, molecular stratification by breast cancer subgroups was significant (P=0.023) for CSS prediction. Especially the differentiation between Her2-positive and Luminal A (HR=4.41, CI 1.53-18.71, P=0.004) and Luminal B (HR=1.96, CI 0.99-4.08, P=0.053) respectively was an independent prognostic parameter for CSS. External validation resulted in comparable risk stratification with differences in fractional subgroups distribution. CONCLUSION: Gene expression of Her2, ESR1, PGR, Ki67 and corresponding breast cancer subtypes allow a risk-stratification in MIBC, whereby Her2 overexpressing tumors reveal a particularly poor prognosis.